EDUCATIONAL PROGRAM OF THE SPECIALIZATION «TECHNICAL AND COMPUTER GRAPHICS» IN EDUCATION AREA «TECHNOLOGY» - Vladyslav Boyko (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The article focuses attention on the problem of school-leavers' professional self-determination, including the conscious choice of the engineering profession and the importance of specialized training in «Technical and Computer Graphics» performed in engineering and technical subjects classes. Structure and content of the educational program «Technical and Computer Graphics» of the given technological speciality and pedagogical conditions for its implementation are given.